Bonaventure on the Soul and Its Powers - Löwe, Can Laurens (Vivarium, 2021)
Abstract This article examines Bonaventure’s account of the soul and its powers, which seeks to strike a middle path between the better-known identity and distinction views of the thirteenth century. Bonaventure contends that the powers of the soul are neither fully distinct from the soul nor completely identical to it. The article argues that Bonaventure’s view comprises four key theses. Bonaventure maintains (i) that the soul’s powers are necessary features of the soul; (ii) that they depend on the soul; (iii) that they are in the same category as the soul; (iv) but that they belong to this category “by reduction” ( per reductionem ). The article also considers an objection to Bonaventure’s view raised by Peter John Olivi.